The ultrasound appearance of the patellar tendon attachment to the tibia in young athletes is conditional on gender and pubertal stage - Ducher, G.; Cook, J.; Lammers, G.; Coombs, P.; Ptazsnik, R.; Black, J.; Bass, S. L. (Journal of Science and Medicine in Sport, 2010)
This cross-sectional study investigated the imaging appearance of the patellar tendon attachment to the tibia in young male and female tennis players of different ages and pubertal status. Forty-four competitive young players, who had been playing tennis at least for 2 years, were recruited from a tennis school and local tennis clubs. All subjects had bilateral ultrasound imaging of the patellar tendon attachment to the tibia. Standard anthropometric measurements, pubertal status and injury history were recorded. Ultrasound appearance of the patellar tendon attachment was categorised into three stages: cartilage attachment, insertional cartilage and mature attachment. Cartilage attachment was more prevalent in boys (32%) and extended further into puberty (until Tanner stage 4) compared to girls (6% and Tanner stage 1). Tendons with Osgood-Schlatter Disease symptoms (n = 3) did not have a cartilage attachment. Imaging appearance commonly seen in young active athletes, consistent with a clinical diagnosis of OSD, was more common in boys and in the pre- and peri-pubertal stages.